Brain Network Activation Technology Does Not Assist with Concussion Diagnosis and Return to Play in Football Athletes - Broglio, Steven P.; Williams, Richelle; Lapointe, Andrew; Rettmann, Ashley; Moore, Brandon; Meehan, Sean K.; Eckner, James T. (Frontiers in Neurology, 2017)
Background: Concussion diagnosis and management remains a largely subjective process. This investigation sought to evaluate the utility of a novel neuroelectric measure for concussion diagnosis and return to play decision making. Hypothesis: Brain Network Activation (BNA) scores obtained within 72-hours of injury will be lower than the athlete’s preseason evaluation and that of a matched control athlete; and the BNA will demonstrate on-going declines at the return to play and post-season time points, while standard measures will have returned to pre-injury and control athlete levels. Design: case-control study Methods: Football athletes with a diagnosed concussion (n=8) and matched control football athletes (n=8) completed a preseason evaluation of cognitive (i.e., Cogstate Computerized Cognitive Assessment Tool) and neuroelectric function (i.e., BNA), clinical reaction time, SCAT3 self-reported symptoms and quality of life (i.e., Health Behavior Inventory and Satisfaction with Life Scale). Following a diagnosed concussion, injured and control athletes completed post-injury evaluations within 72-hours, once asymptomatic, and at the conclusion of the football season. Results: Case analysis of the neuroelectric assessment failed to provide improved diagnostics beyond traditional clinical measures. Statistical analyses indicated significant BNA improvements in the concussed and control groups from baseline to the asymptomatic timepoint. Conclusions: With additional attention being placed on rapid and accurate concussion diagnostics and return to play decision making, the addition of a novel neuroelectric assessment does not appear to provide additional clinical benefit at this time. Clinicians should continue to follow the recommendations for the clinical management of concussion with the assessment of the symptom, cognitive, and motor control domains.